Investigating stress and coping during practice and competition in tennis using think aloud - Swettenham, L.; Eubank, M.; Won, D.; Whitehead, A. E. (International Journal of Sport and Exercise Psychology, 2020)
Aim: The purpose of this study was to examine stress and coping in both competition and practice in tennis and to further investigate gender difference using Think Aloud protocol (TA) in real-time. Method: 16 (8 males and 8 females) competitive tennis players took part. A within groups design was implemented, and participants verbalised their thoughts between points of a championship tie-break during a practice and a competition condition. Data were transcribed verbatim, analysed for stressors (confidence, performance, external, physical) and coping responses (problem, emotion, avoidance) using deductive analysis. A CSAI-2R questionnaire was used to assess anxiety levels prior to practice and competition. Results: CSAI-2R results showed cognitive anxiety significantly increased from practice to competition. Performance-focused coping (e.g. planning, technical) was verbalised most frequently in both conditions. Performance stressors (e.g. outcome, tactics) were verbalised most frequently in both conditions. Males verbalised significantly more performance stress in competition and physical stress in practice. Females verbalised external stress and utilise problem-focused responses more in competition than practice. Problem-focused coping was utilised most for males and females in both conditions. Conclusion: Through the use of a novel data collection method (TA) this study provides context-specific findings within tennis, which support previous research in stress and coping where gender differences occur only for the type of stressor appraised. TA has also been found to be a viable method to assess stress and coping data in tennis. Findings can inform coaches, players, and psychologists about stressors and coping responses utilised during practice and competition.